2013
DOI: 10.1021/ol402914v
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalyzed Direct Glycosylation of Unprotected and Unactivated Carbohydrates

Abstract: Organocatalyzed direct glycosylation of unprotected and unactivated carbohydrates is reported. This process is catalyzed by triphenylphosphine and tetrabromomethane at room temperature under neutral conditions. With this operationally simple protocol thermodynamically favored, glycosides were obtained in a very straightforward reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 49 publications
(16 reference statements)
0
15
0
Order By: Relevance
“…Addition of lithium bromide significantly enhanced the yield in acetonitrile medium. The same group in the following year introduced the concept of organo‐catalyzed glycosylation of unprotected and unactivated glycosides . Here, traces of PPh 3 and CBr 4 were used as the catalyst with LiClO 4 as the essential additive.…”
Section: Glycosylationsmentioning
confidence: 99%
“…Addition of lithium bromide significantly enhanced the yield in acetonitrile medium. The same group in the following year introduced the concept of organo‐catalyzed glycosylation of unprotected and unactivated glycosides . Here, traces of PPh 3 and CBr 4 were used as the catalyst with LiClO 4 as the essential additive.…”
Section: Glycosylationsmentioning
confidence: 99%
“…Knowing from previouss tudies that direct access to ribofuranosides from unprotected ribose was not possible in relevant yield, [14,16] we began the study with a5 -O-monoprotected ribose moiety that could be synthesized and wass table at am olar scale, but was still labile enough to be cleaved in situ by simple treatment with acid. Knowing from previouss tudies that direct access to ribofuranosides from unprotected ribose was not possible in relevant yield, [14,16] we began the study with a5 -O-monoprotected ribose moiety that could be synthesized and wass table at am olar scale, but was still labile enough to be cleaved in situ by simple treatment with acid.…”
Section: Resultsmentioning
confidence: 99%
“…The first neutralg lycosylation conditions subjected glucose, in the presence of an excess of phenol,t oM itsunobu conditions to afford the b-phenolic glycoside in moderate yield and reasonabled iastereoselectivity ( Figure 3b). Much more recently, Mahrwald and Schmalisch developed neutral catalytic conditions to provide aliphatic or benzylic glycosides from several furanoses in good to moderate yield; [14] however,g enerallyt he conditions provided am ixture of anomersa nd often the undesired pyranoside regioisomer prevailed. Much more recently, Mahrwald and Schmalisch developed neutral catalytic conditions to provide aliphatic or benzylic glycosides from several furanoses in good to moderate yield; [14] however,g enerallyt he conditions provided am ixture of anomersa nd often the undesired pyranoside regioisomer prevailed.…”
Section: Introductionmentioning
confidence: 99%
“…[64] In the context of organocatalysis, Mahrwald et al reported in 2013 the glycosylation of unprotected sugars using triphenylphosphine and tetrabromomethane under neutral conditions. [65] A series of unprotected monosaccharides (hexoses and D-ribose) were glycosylated with simple alcohols at room temperature. Glycoside products were obtained after 16 h in low to excellent yields and with poor to good α/ stereoselectivity.…”
Section: Organocatalytic Glycosylations Of Unprotected and Unactivatementioning
confidence: 99%